Rancangan Bangun Sistem Informasi Pengelolaan Penerimaan Peserta Didik Baru di SMA Negeri 1 Tamiang Layang Berbasis Website - Milenia, Tiara Sari; Nugrahaningsih, Nahumi (Universitas Palangka Raya, 2022)
SMA Negeri 1 Tamiang Layang is one of the high schools located in East Barito Regency. The purpose of this research is to build an Information System Website for the Management of New Student Admissions at SMA Negeri 1 Tamiang Layang. The system development method used is the Waterfall model, starting from analysis, design, implementation and testing. The design is using Data Flow Diagrams (DFD) using context diagrams, Level 0 and Level 1 DFDs and Entity Relationship Diagrams (ERD), PHP programming language and MySQL database. The result of the research is that a website for the Management of New Student Admission Management Information System at SMA Negeri 1 Tamiang Layang can be produced that can run and function properly.